Problems of the Current Vaccination Strategy against Hepatitis B - M. V. Konopleva; V. N. Borisova; T. A. Semenenko; M. A. Krymskij (Эпидемиология и вакцинопрофилактика, 2017)
Accumulation of escape mutants of hepatitis B virus (HBV) occur in the many countries at the conditions of wide-scale vaccination against hepatitis B, especially among vaccinated children. The real prevalence of such mutants is underestimated and the capacity of current vaccines to provide cross-immunity against G145R mutant is almost completely absent. The potential for spread of mutant virus strains accumulates. Consequently, a question about the need to change the design of vaccines arises with the purpose of expansion of their action spectrum. An approach of inclusion pre-S epitopes into vaccines has own advantages in fight with escape mutants, but some researchers suggest that the inclusion of modificated a-determinant capable to induce neutralizing antibodies specific to escape mutants into vaccine composition is more preferable. Nevertheless, modification of antigen components of vaccines has certain difficulties related to evaluation of the accuracy of folding of recombinant proteins and their conformity to natural analogues. A recently proposed method for selecting of recombinant antigens possessing the necessary properties likely allows to overcome existing problems. However, apparently, due to the features of species immunity to HBsAg and the limitations of using the chimpanzee model for testing of hepatitis B vaccines, the final answer to this question can only be obtained after clinical studies.